Wild Bees in the City: Reimagining Urban Spaces for Pollinator Health - Burr, Andrea (Consilience, 2016)
Bees (Hymenoptera: Apoidea) are critical to crop production globally. In the last decade, significant declines in pollinator health have been documented and it is now widely considered a “crisis.” The potential causes of reduced pollinator health (species richness and abundance) relate to land-use decisions, practices, and management including habitat fragmentation, lack of foraging resources, pesticides, pests, and disease. Recent studies of native bees found diverse communities in cities around the world. This interdisciplinary pilot study investigates relationships between pollinator health and urban land-uses. It joins ecological and social science field research to examine linkages between native pollinator health and socio-cultural drivers of urban land-use decision-making practices to understand (1) what explains findings of diverse bee species in cities and (2) how citizens can encourage the enhancement of habitat for insect pollinator conservation. To establish a baseline for monitoring pollinator diversity and abundance, wild bees were sampled weekly at designated urban farms, community gardens, and prairie pockets located in St. Louis, Missouri, USA from 2013-2015. Ethnographic interviews were conducted in summer 2015 with 30 decision-makers to learn the social dynamics effecting management at the biologically sampled sites. Informants described bees’ role in crop yield, quality, and quantity; reported planting to attract pollinators; and spoke of the city as viable for pollinator habitat, which is relevant to urban conservation and policy. Their conversational evidence paired with images captured at the research sites reveal the rich urban social-ecological tapestry studied, as well as enhance and inform future research approaches.